2007
DOI: 10.1007/s10147-006-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of chemoradiotherapy for locally advanced esophageal cancer, using daily low-dose 5-fluorouracil and cis-diammine-dichloro-platinum (CDDP)

Abstract: Given the large proportion of patients in this study with inoperable disease (roughly three quarters), our treatment seemed to provide equivalent efficacy and less hematological toxicity than standard-dose chemoradiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 27 publications
2
19
1
Order By: Relevance
“…Although Higuchi et al reported remarkably good results [8], findings from other institutions have remained unchanged [9][10][11][12][13] (Table 4). …”
Section: Discussionmentioning
confidence: 77%
“…Although Higuchi et al reported remarkably good results [8], findings from other institutions have remained unchanged [9][10][11][12][13] (Table 4). …”
Section: Discussionmentioning
confidence: 77%
“…The type of chemotherapy differed significantly among the institutions. In Japan, low-dose protracted infusion chemotherapy combined with full-dose RT of 60-66 Gy used to be a popular regimen for locally advanced esophageal squamous cell carcinomas [5,7,16,20,22]. In the present analysis, full-dose FP was used most frequently (42.5%), followed by low-dose FP (36.8%) ( Table 2).…”
Section: Discussionmentioning
confidence: 84%
“…Various chemotherapy regimens of full-dose FP were included: (1) two cycles of cisplatin 70-80 mg/m 2 (day 1) and 5-FU 700-800 mg/m 2 /day administered as continuous intravenous infusion (IV) (days 1-4 or 1-5) [18][19][20], (2) two cycles of cisplatin 40 mg/m 2 (days 1 and 8) and 5-FU 400 mg/m 2 /day as continuous IV (days 1-5 and 8-12) [6,10], and (3) two or three cycles of cisplatin 60 mg/m 2 (day 1) and 5-FU 400 mg/m 2 /day as continuous IV (days 1-4) [9,21]. Low-dose FP included the following regimens: (1) two cycles of cisplatin 7 mg/m 2 (days 1-5 and 8-12) and 5-FU 250 mg/m 2 /day as continuous IV (days 1-14) [5,18,19], and (2) six weekly cycles of cisplatin 3-5 mg/m 2 (days 1-5) and 5-FU 180-250 mg/m 2 as continuous IV (days 1-5 or 1-7) [19,20,22]. The other regimens included: (1) two cycles of cis-diammine-glycolatoplatinum (Nedaplatin) 55-80 mg/m 2 and 5-FU 300-700 mg/m 2 as continuous IV (days 1-5) [23], and (2) daily administration of 5-FU 300 mg/m 2 /day as continuous IV for 6 weeks [7].…”
Section: Resultsmentioning
confidence: 99%
“…In the booster treatment of 26 Gy, those doses were 21.3, 31.6, and 29.1 Gy, respectively. Chemotherapy consisted of 24-h continuous infusion of 250 mg/m 2 5-fluorouracil and 1-h bolus infusion of 3 mg/m 2 cis-diammine-dichloro-platinum on days when radiotherapy was given, as previously reported [5].…”
Section: Case Reportmentioning
confidence: 99%